In Vitro Assessment Of The Antiplasmodial Activity Of Three Plants Extracts Used In Local Traditional Medicine In Saloum (Senegal) - Ousmane Niass; Serigne Omar Sarr; Baba Dieye; Amadou Diop; Yerim Mbagnick Diop (European Scientific Journal, ESJ, 2016)
Against the scourge of malaria in Africa and the development of chemo-resistance, discovering new natural cures is a major concern for many researchers. As a consequence, the present study was carried out in order, first, to identify the phytochemical compounds, and second, to assess the antiplasmodial activity, of three medicinal plants extracts, selected from an ethno-botany survey conducted in Senegal. The parts of the plants used were Strychnos spinosa (Strychnaceae) leaves and stems, Combretum glutinosum (Combretaceae) barks, and the whole aerial part of Pennisetum polystachion (Poaceae). Among these plants, the hydromethanolic extracts of Strychnos spinosa stems showed the most important activity against Plasmodium falciparum strains, with a IC50 of 15 μg/ml, followed by the leaves chlorophormic extracts and the ethyl acetate extracts of Pennisetum polystachion, with respective IC50 of 20 μg/ml and 21 μg/ml. Combretum glutinosum extracts showed the least important activity, in all tests.